Legal Analysis of Iran’s Economic, Culture and Social Development Planning: From Rational Planning to Wise Decision-Making - Mohammad Sadeghi; Mahdieh Saniee (Journal of North African Economies, 2025)
In today's world, engineering science has placed significant importance on laws related to development, which are crucial to meeting basic human needs. These laws have caught the attention of countries worldwide, and legal experts have been called upon to closely scrutinize the legislative approaches being taken in the economic, social, and cultural development plans of these countries. They are carefully analyzing how these approaches align with distributive and transitional justice elements while considering legal rationality. Recently, there has been a question about whether Iran's existing rational approaches and models in the development planning system align with development laws that respect a rationalist approach and decision-making model. To answer this question, the present study applied a specific methodology based on a literature review, case study, and document analysis of official documents, laws, regulations, and policies related to development planning in Iran. The study analyzed legal rationality, identified potential drawbacks, and proposed approaches to tackle development legal issues.